PREFERENSI KONSUMEN TERHADAP PEMBELIAN SAYURAN ORGANIK DI KOTA PALU - Herlianti Hasan; Abdul Muis; Christoporus Christoporus (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
The purpose of this research was to determine the effect of price attributes, physical perfection, and freshness of organic vegetables on organic vegetable purchase in Palu. The number of samples in this research was 60 people determined by quota sampling technique. Path analysis was used to analyze data. Price, physical performance, and freshness are factors affecting consumers’ preferences to purchase the organic vegetable in Palu.  These three variables have significant effect on the organic vegetable purchase in Palu.  The price, physical perfection and freshness of the vegetables simultaneously had significant effect on purchasing variable with R² equal to 0.763.